2020
DOI: 10.5435/jaaosglobal-d-20-00098
|View full text |Cite
|
Sign up to set email alerts
|

Is the Clinician's Eye a Valid and Reproducible Tool for Diagnosing Patella Alta on a Lateral Knee Radiography?

Abstract: Introduction: Validity and reproducibility of the clinician's eye (CE) to diagnose patella alta (PA) on a lateral knee radiography (radiograph) is unknown. Methods: Cross-sectional study of 46 lateral knee x-rays. Three blind observers used CE, Insall-Salvati (IS), modified Insall-Salvati (mIS), and Caton-Deschamps (C-D) to determine patellar height. Sensitivity and specificity of each observer was compared with the musculoskeletal radiologist's C-D measurements. Intrao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…(1) Sensitivity and specificity of the CE and the “Reference Line” (RL) 2 : As indicated in our introduction, we agree with Dr. Nizić that none of the methods used for the diagnosis of PA is considered a benchmark; therefore, reporting the sensitivity and specificity of a new reference (as the CE and the RL) might be challenging. However, as stated under the methods section of our study, the Caton-Deschamps (C-D) index has already been used to validate the commonly used modified Insall-Salvati ratio (mIS) 3 and is the preferred method of the musculoskeletal radiologist (mskR), who was considered our benchmark for comparison.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…(1) Sensitivity and specificity of the CE and the “Reference Line” (RL) 2 : As indicated in our introduction, we agree with Dr. Nizić that none of the methods used for the diagnosis of PA is considered a benchmark; therefore, reporting the sensitivity and specificity of a new reference (as the CE and the RL) might be challenging. However, as stated under the methods section of our study, the Caton-Deschamps (C-D) index has already been used to validate the commonly used modified Insall-Salvati ratio (mIS) 3 and is the preferred method of the musculoskeletal radiologist (mskR), who was considered our benchmark for comparison.…”
supporting
confidence: 63%
“…The Authors' Reply : The authors appreciate the comments of Dr. Nizić 1 in response to the publication of the above reference regarding the use of the clinician's eye (CE) as a valid method for the diagnosis of patella alta (PA) and agree with its high specificity. The authors would like to address the comments stated in his letter to the editor: (1) Sensitivity and specificity of the CE and the “Reference Line” (RL) 2 : As indicated in our introduction, we agree with Dr. Nizić that none of the methods used for the diagnosis of PA is considered a benchmark; therefore, reporting the sensitivity and specificity of a new reference (as the CE and the RL) might be challenging. However, as stated under the methods section of our study, the Caton-Deschamps (C-D) index has already been used to validate the commonly used modified Insall-Salvati ratio (mIS) 3 and is the preferred method of the musculoskeletal radiologist (mskR), who was considered our benchmark for comparison.…”
mentioning
confidence: 83%
“…The ISR is a measurement of the patellar tendon length in relation to the patella height. [8][9][10][11] In recent comparison studies of patella alta measurements, ISR was demonstrated to be the most sensitive and reliable method for identifying patella alta. 9,10 In this study, a medical student and an attending physician working together used Vaisman et al's method to calculate ISR on X-ray by dividing the distance between the patellar tendon insertion at the tibial tuberosity and the most inferior aspect of the patella by the length between the most superior and inferior aspects of the patella (►Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1 Insall-Salvati ratio (ISR) on lateral X-ray via Vaisman et al ISR is calculated A/B, where A is the distance from the inferior aspect of the patella to the insertion of the patellar tendon at the tibial tubercle and B is the length of the patella from the most superior to the most inferior aspect. 9…”
Section: Methodsmentioning
confidence: 99%
“…To the Editor : I have read with pleasure an article entitled “Is the clinician's eye a valid and reproducible tool for diagnosing patella alta on a lateral knee radiography?” by Dr. Vaisman et al 1 from Chile, published this month in your journal. I hereby express my admiration for a wonderful piece of science they have produced.…”
mentioning
confidence: 95%